The Effect of Animated Video Media on Learning Motivation in Islamic Religious Education Among Grade VIII Students of MTs Rabithatul Ulum Pekanbaru - Hasyiyati, Hasyiyati; Mahnun, Nunu (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Learning motivation plays an important role in supporting the success of Islamic Religious Education (IRE) learning. However, initial observations at MTs Rabithatul Ulum Pekanbaru revealed that students’ learning motivation was still low, characterized by a lack of activity, enthusiasm, and focus during learning. Therefore, this study aims to determine the effect of using animated video media on the learning motivation of Grade VIII students at MTs Rabithatul Ulum Pekanbaru. This study employed a quantitative approach using a pre-experimental design with a One Group Pretest-Posttest Design. The population and sample consisted of 32 students selected through a total sampling technique. Data were collected using a learning motivation questionnaire that had been tested for validity and reliability. Data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, and the Paired Sample t-Test with the aid of SPSS version 25. The results showed that all instrument items were valid (r-calculated > r-table = 0.349) and reliable (Cronbach’s Alpha = 0.840). Descriptive statistics indicated an increase in the mean learning motivation score from 41.37 at pretest to 54.06 at posttest. The normality test confirmed normal data distribution (pretest Sig. = 0.403; posttest Sig. = 0.060). The Paired Sample t-Test yielded a significance value (Sig. 2-tailed) of 0.000 < 0.05, leading to the rejection of H₀ and acceptance of Hₐ. Therefore, it can be concluded that the use of animated video media has a significant effect on the learning motivation of Grade VIII students in Islamic Religious Education at MTs Rabithatul Ulum Pekanbaru.